2020
DOI: 10.1155/2020/5474608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electroacupuncture Treatment at Dazhui (GV14) and Mingmen (GV4) Modulates the PI3K/AKT/mTOR Signaling Pathway in Rats after Spinal Cord Injury

Abstract: Electroacupuncture (EA) is widely recognized as clinical treatment of spinal cord injury (SCI). The purpose of this study is to elucidate whether and how the PI3K/AKT/mTOR signaling pathway plays any role in EA treating SCI. Rats were randomly divided into four equal groups: Control Group, Sham-operation Group, Model Group, and EA Group, then further randomly divided into the following subgroups: 1-day (n=12), 1-day rapamycin (n=6), 14-day (n=18), and 28-day (n=18). A rat model of SCI was established by a modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Gao et al reported that HSP 90 participates in electroacupuncture-induced analgesia in chronic neuropathic pain ( Gao et al, 2021 ). Other signaling pathways, such as PI3K/Akt/Erk, Nogo/NgR, Rho/ROCK, and mTOR, may also include the acupuncture-related beneficial effects against SCI ( Renfu et al, 2014 ; Wei et al, 2018 ; Xiao et al, 2019 ; Li et al, 2020 ).…”
Section: Mechanism Of Acupuncture Therapy In Spinal Cord Injurymentioning
confidence: 99%
“…Gao et al reported that HSP 90 participates in electroacupuncture-induced analgesia in chronic neuropathic pain ( Gao et al, 2021 ). Other signaling pathways, such as PI3K/Akt/Erk, Nogo/NgR, Rho/ROCK, and mTOR, may also include the acupuncture-related beneficial effects against SCI ( Renfu et al, 2014 ; Wei et al, 2018 ; Xiao et al, 2019 ; Li et al, 2020 ).…”
Section: Mechanism Of Acupuncture Therapy In Spinal Cord Injurymentioning
confidence: 99%
“…Some of these signaling pathways have been proven to play important roles in both spinal cord and bone, suggesting their importance in the interaction between bone and spinal cord. For example, activation of the PI3K-AKT-mTOR signaling pathway can improve spinal cord tissue injury and promote bone formation [32,33]. The AMPK signaling pathway is involved in glucose metabolism in the spinal cord and neurons, and its activation can promote functional recovery after spinal cord injury [34].…”
Section: Discussionmentioning
confidence: 99%
“…Electroacupuncture has been used as an alternative treatment for various diseases in recent years ( 42 44 ). A number of studies have shown that EA can improve motor function in the lower limbs of patients with SCI, resulting in improved quality of life ( 32 34 ). However, the mechanism by which EA confers therapeutic benefit is unclear.…”
Section: Discussionmentioning
confidence: 99%